Analysis of Promotional Content on Marketplace Tokopedia and Bukalapak to Improve the Culture of Online Shopping - Tjahjawulan, Indah; Syahnureza, Teuku (Mudra Jurnal Seni Budaya, 2024)
The online marketplace is one of the most prominent players in the e-commerce business in Indonesia. Marketplace sites act as third parties in online transactions by providing places to sell, logistics, and payment facilities. The widespread use of digital platforms in Indonesian society has contributed to the growth of online marketplaces. From early observations of promotional designs on various online marketplaces, they show similarities in the concept of promise, which is content that conveys different moments that need to be celebrated by shopping online with repeated messages and high airing frequency. Then the question arises, why is there a similarity? So it needs to be explored further; what is the content of promotional design on various marketplaces in Indonesia? The promotional content is considered an effective way to encourage consumers to continue shopping, so marketplaces in Indonesia widely use it. The research focused on two leading marketplaces in Indonesia, Tokopedia and Bukalapak, using content analysis methods and comparative studies with digital data collection through Google's search engine facility to find the promotional patterns of the two marketplaces. The results showed similarities in promotional content, including messages, visualizations, and frequency intensity, proving that there is a semblance of content in promotional designs built to improve online shopping culture.